Evaluación del potencial de inóculo de Sclerotium Oryzae en relación con la incidencia de la podredumbre del tallo en arrozales de la Provincia de Corrientes - Cúndom, María Águeda (2010)
Stem rot is a serious disease of rice recorded in most rice-growing regions of the world, and it is one of the most important diseases in the rice producing areas of North-eastern Argentina. The causal agent is often found in the form of sclerotia (Sclerotium oryzae). A large quantity of sclerotia is produced in infected rice leaf sheaths and stems. The sclerotia can be incorporated to the soil through different management practices and are able to survive several years in rice straw or in the soil. The aim of this study was to evaluate the number and viability of sclerotia of S. oryzae present in the soil before planting and their relationship with the intensity of stem rot in the crop (2007-2008 and 2008-2009). Each year, soil samples were collected from 23 production fields in Corrientes province in order to evaluate the number of viable sclerotia by the Krause and Webster technique. The scale proposed by the same authors has been modified and used to estimate the disease level at development stages M7-M8. The population of S. oryzae showed a great variability among the different rice-growing zone, departments and even among the distintc lots within a same field. The number of viable sclerotia per gram of soil ranged from 0.025 to 1.03. The incidence and severity ranged were between 1.02 to 87% and 1.01 to 2.47, respectively. Data analyzed trough Pearson coefficients showed significant positive correlation between stem rot intensity and viable sclerotia by field and year.